2017
DOI: 10.1097/icu.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokines and treatment algorithms in retinopathy of prematurity

Abstract: Purpose of review Currently, severe ROP is diagnosed by clinical evaluation and not a laboratory test. Laser is still considered standard care. However, anti-VEGF agents are being used and there are questions whether and/or if to use them, what dose or type of agent should be considered and what agent may be most beneficial in specific cases.Also unclear are the effects of laser or anti-VEGF on severe ROP, refractive outcomes or infant development. This article reviews recent studies related to these questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Although prematurity and oxygen exposure are central in the etiology of ROP, neonatal inflammation and infection may have a deleterious impact on retinal angiogenesis, aggravating the risk of ROP [ 114 , 115 ]. Pro-inflammatory cytokines, such as TNF-α and IL-6, as well as vascular endothelial growth factor (VEGF) and insulin-like growth factor 1 (IGF-1) are associated with dysregulated vascularization [ 20 , 114 ]. S. epidermidis is one of the prevalent pathogens of endophthalmitis in adults, indicating its potential to cause ocular inflammatory injury [ 116 ].…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…Although prematurity and oxygen exposure are central in the etiology of ROP, neonatal inflammation and infection may have a deleterious impact on retinal angiogenesis, aggravating the risk of ROP [ 114 , 115 ]. Pro-inflammatory cytokines, such as TNF-α and IL-6, as well as vascular endothelial growth factor (VEGF) and insulin-like growth factor 1 (IGF-1) are associated with dysregulated vascularization [ 20 , 114 ]. S. epidermidis is one of the prevalent pathogens of endophthalmitis in adults, indicating its potential to cause ocular inflammatory injury [ 116 ].…”
Section: Retinopathy Of Prematuritymentioning
confidence: 99%
“…The use of anti-VEGF agents in the management of ROP is becoming increasingly popular globally, [33][34][35] including in this study where, in the absence of lasers, it was the primary treatment in most infants (92.3%). Advantages of anti-VEGF treatment over laser include that it is quicker to administer, can give early resolution of active disease, and may be associated with fewer cases of early-onset high myopia.…”
Section: Discussionmentioning
confidence: 84%
“…ROP is caused by impaired autoregulation of the retinal blood vessels and sudden postnatal oxygen tension. Retinal neovascularization in ROP cases involves angiogenic factors such as VEGF in preterm infants and VLBW infants [ 20 - 22 ]. Recent studies have reported that lower GA, lower birth weight, and excessive oxygen exposure are major risk factors for ROP [ 20 - 23 ].…”
Section: Discussionmentioning
confidence: 99%